Earthship Freo: A Case Study of the Potential and Limitations of Participatory Documentary Filmmaking - Johnston, Michelle; Shardlow, Mignon (Peter Lang, 2024)
The reality of anthropogenic climate change can no longer be ignored or disputed. Global warming’s disruption of the fragile conditions required for humans to thrive requires urgent action. Academics, public intellectuals, journalists and filmmakers have a responsibility to inform, motivate and empower people to take action for the sake of the long-term survival of life on earth. This chapter describes a fragment of that effort: an attempt to understand better the potential and limitations of participatory documentary filmmaking in fostering active hope and transformative action. Documentary films have an important role to play in how we see the world, educate ourselves, and develop empathy with the lived experiences of others. Participatory documentary in particular has an important role to play because it is not just about producing stories, it is about a storytelling process that respects and reflects the voices and agency of people in the story. It encourages participants to tell their own story and allows them veto over storylines. This can limit the documentary maker’s ability to craft the most emotive and ‘perhaps’ engaging narrative – and therefore may limit the potential power of the film to change minds and create change – but it can also enable a perspective that allows for complexity and invites viewers to engage on a more personal level. This chapter features a case study of a feature documentary, Earthship Freo, and explores the capacity for participatory documentary filmmaking to create social change. In particular, it describes how the filmmakers navigated their passion for environmental advocacy, ethical considerations, truthful representation, and a desire to tell a story that appeals to an audience. The filmmakers and authors of this chapter are also university academics: Michelle Johnston is a documentary filmmaker, and Mignon Shardlow, a journalist. They explore the advantages and limitations of this approach to documentary filmmaking and associated ethical considerations. The authors have also incorporated insights from interviews with two award-winning documentary filmmakers conducted specifically for this chapter.